(untitled) (Research, Society and Development, 2022)
Trafficking in persons features a severe violation of Human Rights whereas sets up a contemporaneous mode of slavery as turn your victims into goods. This research seeks to detail this crime by the light of Palermo Protocol and understand the influence brought by this politics of fighting trafficking in persons caused in the extraditions environment. Starting with the publication of this Protocol, slowly, there has been a standardization of the south American legislation, enlarging the knowledge of the various shapes that human trafficking can assume. Starting with the hypothesis that this standardization brought by the Protocol could mean the facilitation of the extradition, it was performed as an empirical dialectical research, along with documental research in the Brazilian Supremo Tribunal Federal and in the other south American Supreme Courts. The scarcity of jurisprudence is notable. However it was possible to realize that the extraditions were on the bilateral conventions, thus, the Palermo Protocol wasn’t explicitly mentioned on the granting of the extradition demands. Besides that, except the Bolivarian Republic of Venezuela, all the south American countries have a legislation on human trafficking including all shapes of this crime as contained in the Protocol. The conclusion from this information is that the standardization has contributed to the granting of the extradition requests, because one of the requirements in the bilateral conventions is the need for double incrimination. Therefore, if all the countries have the same conceptions of human trafficking in their legislations, the requirement of double incrimination will always be filled.